Real Options in Evaluation of Investment Decisions - Leshchiy, Lesya (Opcje rzeczywiste w ocenie projektów inwestycyjnych, 2010)
Real options capture the value of managerial flexibility to adapt decisions in response to unexpected market developments. Companies create shareholder value by identifying, managing and exercising real options associated with their investment portfolio. The real options method applies financial options theory to quantifying the value of management flexibility in a world of uncertainty. If used as a conceptual tool, it allows management to characterize and communicate the strategic value of an investment project. The use of real options is particularly relevant when the total investment will be made on a phased basis and the subsequent investments depend on the situation at the particular time when they are to be made. Such investments have to be reassessed prior to the expiry of the option when a better assessment of the likely returns may be possible.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 145, s. 75-79
Keywords: real options; evaluation; investment; decisions